PERILAKU COST STICKINESS DALAM KOMPENSASI EKSEKUTIF BANK BUMN DAN NON BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Setiawati, Luh Pande Eka; Rasmini, Ni Ketut; Mimba, Ni Putu Sri Harta (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.05.TAHUN 2017, 2017)
This study aims to prove empirically that an increasing percentage of cash compensation received by executives of banks when the bank's revenue increase was higher compared with the percentage decrease in cash compensation received when the bank's revenue declined (sticky cost behavior). As well as to see the different levels of sticky cost in executive compensationstate BUMN Bank and non BUMN Bank that listed in the Indonesia Stock Exchange . This study uses secondary data . Sampling technique used purposive sampling. Total samples is as many as 31 companies . Data analysis technique used is the analysis of multiple linear regression and Mann Whitney test . The analysis showed that an increasing percentage of cash compensation received by executives of banks when the bank's revenue increase was higher than the percentage decrease in cash compensation received when the bank's revenue declined or there are cost stickiness behavioral on executive compensation further results of the study showed no difference in the level of cost stickiness on executive compensation BUMN Banks and non BUMN.
Keywords: Cost Stickiness, Executive Compensation, BUMN, Non BUMN